Didactic Situations in Fraction Learning with PhET Colorado for Seventh Grade Students - Ira, Ira Kurniawati; Imam Sujadi; Riki Andriatna; Arum Nur Wulandari; Yuli Bangun Nursanti (Universitas Pendidikan Ganesha, 2025)
This research problem focuses on identifying the characteristics of didactical situations in learning fraction concepts that involve interactions between teachers, students, and materials. This research aims to analyze how didactical situations can support more effective and meaningful learning through the use of technology, particularly Colorado PhET simulation. This research is descriptive qualitative research with case study design. The research subject was a seventh grade junior high school mathematics teacher who was selected by purposive sampling. Data were collected through observations, interviews, and tests to understand the dynamics of learning. The instruments used were interview guides, observation sheets, and test questions. The data were analyzed using a thematic analysis approach to identify patterns in the interaction of teachers, students, and learning materials. The results showed that the characteristics of the didactical situation in learning the concept of fractions include: (1) learning that supports students' independent knowledge construction; (2) cooperative learning; (3) use of contextual problems relevant to the concept of fractions; (4) optimization of PhET Colorado to evaluate students' understanding; and (5) use of scaffolding by teachers to strengthen concept understanding. The conclusion of this research is that the didactical situation built can improve the effectiveness of mathematics learning and students' understanding of fraction concepts. The implication of this research can provide an alternative for teachers in designing more interactive and meaningful learning by utilizing technology in didactical situations.